2018
DOI: 10.1016/j.aott.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic comparison of bilateral patellar tendon dimensions in patients treated via intramedullary tibial nailing using a transpatellar approach

Abstract: Level IV, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
1
1
1
Order By: Relevance
“…Obremsky et al reported a 48% incidence of anterior knee pain following IMN in their study [17]. Similarly, Erinç et al found that 46.2% of patients experienced this pain in their local study [18]. In our study, only 19 out of 57 patients who underwent tibial IMN reported anterior knee pain, accounting for 33.3% of the sample population.…”
Section: Discussionsupporting
confidence: 53%
“…Obremsky et al reported a 48% incidence of anterior knee pain following IMN in their study [17]. Similarly, Erinç et al found that 46.2% of patients experienced this pain in their local study [18]. In our study, only 19 out of 57 patients who underwent tibial IMN reported anterior knee pain, accounting for 33.3% of the sample population.…”
Section: Discussionsupporting
confidence: 53%
“…Firstly, knee pain is common in patients who undergo IMN fixation for tibial shaft fractures. 29,30 In the present study, the average VAS at 1 month postoperative was 1.8 in MITR group, which is significantly lower than that of the conventional manual traction group with 2.8 (P<0.001). Secondly, although we did not observe the faster fracture healing process in the MITR group, the application of MITR resulted in a higher HSS score (90.8 vs 86.4, P<0.001).…”
contrasting
confidence: 50%
“…Therefore, the thicker and wider tendon is less related to knee pain. 24 Very scarce literature has been observed regarding the nail tip positioning during IM/IL, which can result in lesser anterior knee pain. This study bridges this gap in literature contributing to the knowledge about the nail tip positioning for tibial shaft fractures resulting in less pain and morbidity.…”
Section: Discussionmentioning
confidence: 99%